Building a Safer and Faster CAR: Seatbelts, Airbags and CRISPR - Perales, Miguel-Angel (Biol Blood Marrow Transplant, 2017)
Therapeutic T cell engineering has recently garnered widespread interest owing to the success of CD19 (Chimeric Antigen Receptor) CAR therapy. CARs are synthetic receptors for antigen that redirect the specificity and reprogram the function of the T cells in which they are genetically introduced. CARs targeting CD19, a cell surface molecule found in most leukemias and lymphomas, have yielded high remission rates in patients with chemorefractory, relapsed disease, including acute lymphoblastic leukemia, chronic lymphocytic leukemia and non-Hodgkin lymphoma. The toxicities of this treatment include B cell aplasia, cytokine release syndrome (CRS) and neurotoxicity. Although reversible in most instances, these toxicities may require specific medical interventions, including transfer to intensive care to treat severe CRS. Guidelines for managing these toxicities are emerging. The recent report of a non-human primate model for CRS is poised to help advance the management of this syndrome. Finally, new engineering modalities, based on the use of targeted nucleases like CRISPR, may further enhance the efficacy and safety of CAR T cells.